Analisis Kualitas Jaringan Internet pada SMK Menggunakan Metode Quality of Service - M. Septrio Rafinaldo; Iwan Iskandar; Nazruddin Safaat Harahap; Reski Mai Candra (STMIK Budi Darma, 2023)
One of the most common uses of Internet technology is in the field of education. The utilization of the Internet in education has long been employed by SMK Negeri 1 Tembilahan. This school utilizes internet connectivity as a tool and means to support the teaching and learning process. Therefore, the school must provide a reliable network service to ensure smooth learning experiences. This research aims to evaluate the quality of internet connectivity at SMK Negeri 1 Tembilahan using the Quality of Service (QoS) method with parameters such as throughput, delay, packet loss, and jitter. The study also analyzes the internet quality in each department of SMK Negeri 1 Tembilahan during peak and off-peak hours, involving both teachers and students as users. With a total of 1,307 users, the school utilizes an internet connection from an Indihome provider with a bandwidth of up to 300 Mbps. The test results indicate that the throughput, packet loss, delay, and jitter values are rated at index 4, categorized as